Exploring the Nexus Between Human Capital, Corporate Governance and Performance: Evidence from Islamic Banks - Nawaz, Tasawar (Journal of business ethics, 2019)
This paper offers novel insight into the Islamic banking business model by considering the effect of investments in human capital and corporate governance features on the market performance of Islamic banks. Based on a sample of 47 banks (30 full-fledged Islamic banks and 17 Islamic Shariah-windows) operating in different regions during the 2005–2010 period, and controlling for firm-specific characteristics, this paper finds investments in human capital to have a significant positive impact on the market value in the pre- and post-financial crisis period. Based on a market measure, this paper finds board size and CEO power to have a significant positive impact, while the size of Shariah Supervisory Board (SSB) has the opposite effect on market performance. The results further reveal that the Islamic banking sector is not a homogeneous group, with full-fledged Islamic banks having lax corporate governance mechanisms and large size, while their counterparts, Islamic Shariah-windows, having strong corporate governance mechanisms tend to invest more in human capital to yield positive market value. Overall, the analysis suggests that the financial crisis may have further spurred the impact of investments in human capital on the market performance.